Peranan Pemerintah Desa dalam Pencegahan Stunting di Desa Aek Mual Kecamatan Siabu Kabupaten Mandailing Natal Tahun 2023 - Ritonga, Soritua; Pasaribu, Safran Efendi (Universitas Muhammadiyah Tapanuli Selatan, 2023)
Based on Basic Health Research data for 2019, the stunting rate in Indonesia is 27.67%. According to WHO, a public health problem is considered chronic when the prevalence of stunting exceeds 20%. Villages are required to develop programs or activities related to stunting prevention. So the researchers wanted to know the role of the village government of Aek Mual in preventing stunting, so the researchers conducted research on the role of the village government in preventing stunting in Aek Mual Village, Siabu District in 2023. The technique for selecting research subjects was carried out by purposive sampling, which obtained several subjects, namely village officials. Aek Nausea, mothers who have toddlers and village midwives. Data collection techniques were carried out by direct interviews with informants using interview guidelines. From the results of the study it can be concluded that the role of the village government in preventing stunting, especially health, has been carried out well. Both the allocation of funds and the actions and ideas made by the Aek Mual Village Government have prevented Aek Mual Village from stunting, the village government's efforts such as providing additional food, carrying out toddler sweeping activities, child immunization and providing additional food to pregnant women.